Effects of initial three-dimensional electron energy distribution on terahertz Bloch oscillations in a biased semiconductor superlattice. (1st March 2023) - Unuma, Takeya; Ueda, Kosuke; Okamoto, Ryuichi
Abstract: We investigate how the initial three-dimensional energy distribution of electrons created by femtosecond pump pulses in a biased semiconductor superlattice affects terahertz Bloch oscillations, which imitate a step response to a bias electric field. The emitted terahertz waveforms are well reproduced from a damped oscillation current with capacitive nature, exhibiting shorter relaxation times and worse temporal resolutions for central pump photon energies that are outside the range of ordinary electron excitation into the conduction first miniband. This indicates that in-plane excess energy changes the relaxation time via scattering processes, while partial use of the pump pulse spectrum reduces the temporal resolution.